2011
DOI: 10.1007/s10750-011-0944-5
|View full text |Cite
|
Sign up to set email alerts
|

Reuse potential of phosphorus-rich filter materials from subsurface flow wastewater treatment filters for forest soil amendment

Abstract: The aim of this study was to test P-enriched filter materials from a wastewater treatment experiment regarding their fertilizing efficiency in pot experiments with silver birch (Betula pendula Roth.) seedlings. Tested materials included hydrated calcium-rich oil shale ash and well-mineralised peat. A mixture of peat and hydrated ash demonstrated the best results: seedlings grown on that mixture had the highest P concentration and an optimal N:P:K ratio in leaves. Hydrated ash has a low concentration of heavy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The reduction of P in well-mineralized peat may have been caused by the sorption, sedimentation and combination of complex compounds . High P removal with hydrated oil shale ash was also demonstrated in other studies in which various wastewater types were used (Liira et al, 2009;Vohla et al, 2011;Kõiv et al, 2012;Karabelnik et al, 2012). Several experiments indicate that the capacity of hydrated oil shale ash sediment to remove phosphorus is very high, up to 65 mg P g À1 (Kaasik et al, 2008;Liira et al, 2009).…”
Section: System Treatment Efficiencysupporting
confidence: 59%
See 1 more Smart Citation
“…The reduction of P in well-mineralized peat may have been caused by the sorption, sedimentation and combination of complex compounds . High P removal with hydrated oil shale ash was also demonstrated in other studies in which various wastewater types were used (Liira et al, 2009;Vohla et al, 2011;Kõiv et al, 2012;Karabelnik et al, 2012). Several experiments indicate that the capacity of hydrated oil shale ash sediment to remove phosphorus is very high, up to 65 mg P g À1 (Kaasik et al, 2008;Liira et al, 2009).…”
Section: System Treatment Efficiencysupporting
confidence: 59%
“…P removal by ash sediment mostly takes place through Ca-phosphate precipitation and the formation of insoluble calcium phosphate complexes (Ca 3 (PO 4 ) 2 ), while the reduction of P in well mineralized peat is caused by the sorption, sedimentation and combination of complex compounds (Kõiv et al, 2010). A number of small-scale short-term, in-and outdoor experiments have been carried out where peat and hydrated oil shale ash was used for different wastewater treatments (Liira et al, 2009;Vohla et al, 2005Vohla et al, , 2011Kõiv et al, 2012;Karabelnik et al, 2012), however, year-long investigations are missing.…”
Section: Introductionmentioning
confidence: 99%
“…A fraction with higher concentrations of SiO2 and Al2O3, compared with other solid waste resulting from oil shale processing can be used as an additive in ordinary Portland cement. However, other fractions of ashes are exposed to hydraulic transportation in a slurry with a water-to-ash ratio of 20:1 in sedimentation ponds, creating mountain plateaus in Estonia occupying an area of more than 20 km 2 and containing more than 300 Mt of ashes [104][105][106]. The physical, chemical, and mineralogical properties of oil shale ashes are quite widely studied Oil shale comprises organic, carbonate, and terrigenous material at various proportions, but high calcium content (CaO content as high as 55%) guides for valuable utilization of this waste [101].…”
Section: Solving the Problem Of Oil Shale Wastementioning
confidence: 99%
“…phosphate-solubilizing bacteria, Richardson, 2001) and phosphate-solubilizing fungi (Whitelaw, 1999). Other research demonstrated that plant root exudates produce organic acids that are strong enough to dissolve P even from hydroxyapatite and the P-saturated filter materials could be source of slow release P (Cucarella et al, 2007;Kõiv et al, 2012).…”
Section: Preliminary Design Of the Hybrid Treatment Systemmentioning
confidence: 99%